Intensive Care of Hypervolemia of Lesser Circulation after Rastelli Procedure Carried out for the Patient with a Pulmonary Atresia - R. A. Ibadov; H. K. Abrolov; L. A. Nazirova; D. I. Julamanova; A. Sh. Arifjanov; N. A. Strijkov; S. Kh. Ibragimov (Общая реаниматология)
17yearold patient with hypervolemia of lesser (pulmonary) circulation was operated for tetralogy of Fallout with pulmonary atresia. She was successfully treated by intensive therapy using techniques of noninvasive ventilation with regard to clinical status of hypovolemia of the lesser (pulmonary) circulatory system in the early post operative period.